Tipologi Transformasi Fasad Rumah Bantuan Pasca Tsunami di Desa Deah Baro, Kecamatan Meuraxa, Banda Aceh, Indonesia - Zamzami; Marlisa Rahmi; Maysarah Binti Bakri (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2025)
Meuraxa sub-district was one of the areas significantly affected by the 2004 Aceh tsunami. After the disaster, housing assistance was provided by variousinternationalagencies and organizations, in the same location. Initial observation indicate changes in the facades of the aid houses. Threfore, ths study aims to identify the factors that causedthe transformation of the facade and to determine the dominant elements that underwenttransformation in post-tsunami relief houses in Meuraxa Sub-district, Banda Aceh.